Prehospital Telemedical Emergency Management of Severely Injured Trauma Patients - Eder, Patrick A.; Reime, Birgit; Wurmb, Thomas; Kippnich, Uwe; Shammas, Layal; Rashid, Asarnusch (Methods of Information in Medicine, 2018)
Background Trauma is a global burden. Emergency medical services (EMS) provide care for individuals who have serious injuries or suffered a major trauma.Objective This paper provides a comprehensive overview of telemedicine applications in prehospital trauma care.Methods We conducted a systematic review according to PRISMA guidelines. We identified articles by electronic database search (PubMed, EMBASE, the Cochrane Library, CINAHL, SpringerLink, LIVIVO, DARE, IEEE Xplore, Google Scholar and ScienceDirect) using keywords related to prehospital settings, ambulance, telemedicine and trauma. Search terms and inclusion criteria were specified a priori by the PICOS template and revised throughout a configurative approach iteratively, to outline the complexity and variety of different telemedical concepts.Results A final sample of 15 records was systematically selected. Most interventions were piloted and/or evaluated in Germany for trauma victims in prehospital settings. Six studies were simulated scenarios. Telemedical assistance (TMA) via real-time telemetry systems (RTS), enabling video and audio conferencing between EMS by tele-emergency physicians (TEP) were associated with a higher treatment quality and a shorter time-to-treatment in invasive procedures. By initiating in-hospital preparations based on telemedical prehospital notification (TPN), loss of information during the clinical handover was reduced and in-hospital protocols were activated with high accuracy. Remotely guided ultrasound (Tele-Ultrasound) by TEP showed an overall high diagnostic accuracy in simulations. Technical solutions were reliable, seemed practical and auspicious.Conclusion The review indicates that TMA and TPN are accompanying telemedical concepts in out-of-hospital trauma care. Well-designed populated studies are needed to fully assess the effect of telemedicine in acute trauma care. Therefore, evidence regarding the effectiveness of telemedicine in prehospital setting for trauma patients is still limited.
Keywords: telemedicine; EMS; ambulance; acute trauma care; systematic review